A closer look at rickets and vitamin D deficiency in Manitoba: The tip of the iceberg. Issue 3 (13th August 2018) - Lautatzis, Maria-Elena; Sharma, Atul; Rodd, Celia
Abstract: Objectives: Vitamin D deficiency rickets remains a problem in Canada. Our primary objective was to determine the annual incidence of rickets and/or early vitamin D deficiency in Manitoba. Secondarily, we investigated if there was an increase in the annual incidence. Methods: A retrospective chart review was undertaken to identify cases in our catchment area from 2003 to 2015. Data sources included endocrine and hospital charts and radiology reports. Early vitamin D deficiency was determined by review of all 25(OH)D tests from 2011 to 2015. Values less than 30 nmol/L with an elevated bone marker prompted a chart review in children under 7 years. Results: We identified 46 cases of rickets and 68 with early vitamin D deficiency. For Manitoba, the annual incidence of rickets was 8.2 cases per 100, 000 in infants, and 1.6 per 100, 000 in children aged 1 to 7 years. Those with early vitamin D deficiency had annual incidences of 2.7 per 100, 000 infants and 9.9 per 100, 000 Manitoban children. No temporal trends were noted for either. For both disorders, most cases were from northern or rural locales; about 50% were of self-declared Indigenous or Inuit heritage, and the majority (>75%) of children were from families with high material deprivation using area-based socioeconomic measures. Conclusion: Despite several decades of preventative efforts, the incidence of rickets was comparable to previous Canadian reports, particularly in infants. Greater education across the lifespan and engagement with communities and public health agencies will be needed to reduce the high incidence of this preventable disease.